ESTUDIO EXPERIMENTAL DE LAS CARACTERISTICAS FISICO-MECANICAS DE LOS TAPONES DE CORCHO NATURAL - Hernández Fernández, Antonio (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The present experimental study tries to evaluate the best way to cuantify cap natural cork quality by standardized experiments measuring different physical and chemical parameters. Within the cork sector, the cap industry is the broadest extended and the most representative, since it represents the most significant manufacture. Its economic value is a 70-80% of the final sale price. This study is referred to the cilindric cap, made from natural cork, boiled in water at 100°C, at atmospheric pressure.
Keywords: CAP; Cork; Physical and Chemical parameters; Standardization